Undiscovered, yet Necessary: Love in In the Shadow of Altars by Vincas Mykolaitis-Putinas - Cibarauskė, Virginija; Jevsejevas , Paulius (Semiotika, 2015)
The article presents a semiotic inquiry into a particular rendering of the theme of love. The object of analysis is a novel by Vincas Mykolaitis-Putinas, In the Shadow of Altars (Altorių šešėly; 1933), one of the first and most prominent Lithuanian novels about love (it involves Liudas Vasaris, the protagonist, ‘breaking free’ from being first a seminary student and then a priest, to being a poet and a married man). Prior critique of the novel highlights the psychological-existential character and thematic autonomy of love therein. However, the outcome of the present analysis is quite the opposite: in the novel, love stories are actually organized according to fairytale principles of narrative structure, and developed on the basis of sociocultural stereotypes that do not imply any direct experience or an existential dimension. Our research employed a number of theoretic and methodological supports: R. Barthes’ notion of figure, presented in Fragments d’un discours amoureux; 1977, A. J. Greimas’ canonical narrative schema, developed on the basis of fairy-tale research, and Y. Lotman’s notion of worldview, presented in his works on individual selfperception and behavior patterns. These devices were applied according to the specific character and structural unity of the text. Structural analysis of sections devoted to love stories and of their relation with other sections reveals that love in this novel is not important per se, but as a means of becoming of a man-creator. The becoming of Liudas Vasaris as a creator – a utopian image of personal fulfillment in one’s own society – is made possible in the novel by the exploitation of a fairy-tale love narrative. Therefore, the novel presents a ‘love tale’ rather than a love story rendered by novelistic narration. This also determines the thematic treatment of love. In the Shadow of Altars love does not become an independent theme, problem or value; it is dissociated both from the novel’s historic-sociocultural framework and from any manifestations of subjectivity. Love situations are composed by reproducing sociocultural and literary stereotypes of behavior and perception, thus unconsciously propagating underlying patriarchal notions and rituals. Therefore, the results of this inquiry call for an adjustment of In the Shadow of Altars’ critical reception, a re-evaluation of the novel’s character and of the possibilities for an adequate reading. This also encourages broader questions about love in Lithuanian literature, from the possibilities of its existence to its authenticity. Furthermore, recognizing the primacy of the story of becoming of a man-poet allows for an identification of the tensions and polemic between poetic currents in the Lithuanian literary field of the first three decades of the 20th century. The trajectory of becoming of Vasaris-poet begins with an orientation towards a ‘poetry of ideas’, continues into a stage of decadent neo-romanticism (an important element of the latter stage are decadent relations with decadent women), and ends its development with a program of hypothetical harmonious neo-romanticism (together with the discovery of ‘truthful’ love and way of life). In this sense, this analysis is a contribution to ongoing research of interaction between textual and non-textual structures, text and context, semiotics and cultural studies.